SYNTHESIS AND CHARACTERISTIC OF NANOSILICA FROM GEOTHERMAL SLUDGE: EFFECT OF SURFACTANT - Adiatama, Aufa Rai; Susanti, Ratna Frida; Astuti, Widi; Petrus, Himawan Tri Bayu Murti; Wanta, Kevin Cleary (National Research and Innovation Agency (BRIN), 2022)
In the synthesis of nanoparticles, the phenomenon of agglomeration is an undesirable condition because the particles formed can be larger. The use of surfactants can prevent the occurrence of this phenomenon. In this study, the use of surfactants was studied in the synthesis of nanosilica from geothermal sludge. The method applied in the synthesis of nanosilica is the sol-gel method. A 1 M sodium hydroxide (NaOH) solution was used to prepare the sol phase, while the gel phase was prepared at pH 5 using a 1.5 M hydrochloric acid (HCl) solution. The surfactants used were alkyl benzene sulfonate (ABS), cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), and polyvinylpyrrolidone (PVP). The surfactant added to the precursor solution was at the critical micelle concentration (CMC), where the CMC values for each surfactant were 0.15, 0.05, 0.50, and 1.00 wt% for ABS, CTAB, SDS, and PVP, respectively. The experimental results showed that the synthesis of nanosilica without surfactant could produce the product with a purity of 98.03%. Even though the purity is already high, the resulting product experiences agglomeration and surfactants were needed to minimize the occurrence of agglomeration in the product. The surfactant that gives the best product quality is PVP, where the particle size is in the range of 2.01–3.65 nm. However, the product produced with this PVP has a low purity, 56.67%. It is because the sodium chloride (NaCl) is trapped in the surfactant template.